PENGARUH FASILITAS KERJA, KEDISIPLINAN DAN PENGAWASAN TERHADAP KINERJA PEGAWAI DINAS PERIKANAN KOTA TANJUNGBALAI - Elfina Manurung; Eko Topan Prihatin Nura; Nurdin .; Tengku Anggi Metia; Isminingsih . (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this research is: How do work facilities, discipline and supervision influence the employees performance at Dinas Perikanan Kota Tanjungbalai. This study aims to determine the effect of work facilities, discipline and supervision on employee performance. With total sampling technique, the sample in this study was 41 people. The results showed; Work facilities partially have a positive effect on employee performance; Discipline partially has a positive effect on employee performance; Partial supervision has a positive effect on employee performance; Work facilities, discipline and supervision have a positive and significant effect on employee performance.